CYSTIC FIBROSIS IN AN ADULT – A RARE CASE – DIAGNOSED AND CONFIRMED BY A NEW, NOVEL, INDIGENOUS TECHNIQUE - Sharma, Raghava; Raj, Raghu; Shetty, Sukanya (Journal of Health and Allied Sciences NU, 2012)
Cystic fibrosis (CF) is an important autosomal recessive disorder caused due to genetic mutation thus affecting the chloride channel. It involves multiple systems particularly lungs, respiratory tract and gastro intestinal tract. It is mainly considered as a disease of pediatric population. However it is being reported from adult population, more frequently from the western countries due to better survival.CF is reported very rarely from India and report of adult CF is much more rarer. Conformation of CF is by HRCT (High resolution computerized tomography), gene mutation analysis and sweat chloride estimation. However sweat chloride test presently being employed (called pilocarpine iontophoresis ) is costly, very complicated and is not available even in most advanced centers in India.Our case highlights the need for a high index of suspicion for suspecting CF in adults with chronic respiratory symptoms, and the need for a cost effective, easily available, reproducible, standardized test technique for sweat chloride estimation.Here with we present a case of CF (cystic fibrosis) in an adult male of 23 years whose diagnosis was confirmed by a new novel indigenous technique of Sweat chloride estimation.
Keywords: Cystic fibrosis; Adult Cystic fibrosis; Sweat chloride estimation; New novel indigenous technique of Sweat chloride estimation.